Renal cell carcinoma in a horseshoe kidney treated with robot-assisted partial nephrectomy - Yamamichi, Gaku (Urol Case Rep, 2019)
Horseshoe kidney is one of the most common congenital renal fusion anomalies and the incidence of renal cell carcinoma in horseshoe kidney is predicted to be approximately 5.2/100000 individuals. Because horseshoe kidney merges malformations and vascular changes, open surgery is the standard for treatment. There are no reports of robot-assisted partial nephrectomy (RAPN) for renal cell carcinoma in horseshoe kidney. We describe for the first time the safety and the utility of RAPN in a horseshoe kidney with renal cell carcinoma.